A three-dimensional Mn-based MOF as a high-performance supercapacitor electrode. Issue 7 (23rd January 2023) - Rong, Hongren; Song, Peng; Gao, Gexiang; Jiang, Qingyan; Chen, Xiaojuan; Su, LiXin; Liu, Wen-Long; Liu, Qi
Abstract : A 3D Mn-based MOF [Mn(BGPD)(H2 O)2 ] (Mn-BGPD) was synthesized. The asymmetrical supercapacitor of Mn-BGPD exhibits an excellent energy density and better cycling stability. Abstract : Developing new high-performance electrode materials for improving the energy density of supercapacitors is an important task. Herein, a new three-dimensional (3D) metal–orgainc framework (MOF) [Mn(BGPD)(H2 O)2 ] (Mn-BGPD; BGPD = N, N ′-bis(glycinyl)pyromellitic diimide) was synthesized. When Mn-BGPD is used as the electrode material of supercapacitors, in a three-electrode setup, it shows an outstanding specific capacitance of 832.6 F g −1 at a current density of 1 A g −1 . The asymmetrical supercapacitor of Mn-BGPD shows an attractive specific capacitance of 100 F g −1 at 1 A g −1, which corresponds to an excellent energy density of 35.5 W h kg −1 . Moreover, better cycling stability with a capacitance retention of 46.7% is also shown. The high electrochemical performance makes Mn-BGPD a very promising electrode material for supercapacitors.